1999
DOI: 10.1051/analusis:1999134
|View full text |Cite
|
Sign up to set email alerts
|

The synergetIc effect of redox mediators and peroxidase in a bienzymatic biosensor for glucose assays in FIA

Abstract: Amperometric biosensors based on enzymes are interesting due to their high sensitivity, excellent selectivity, simplicity, low cost and rapid response. The most frequently used enzymatic methods for glucose determination employ glucose oxidase (GOD), due to its high selectivity towards ß-D-glucose. In the presence of GOD, the oxidation of glucose occurs, producing H 2 O 2 . Most commonly, the electrochemical detection is performed through the anodic oxidation of H 2 O 2 [1]. A drawback with this detection tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Similar procedures are being utilized in stripping analysis, where the beneficial effect of the preconcentration step at a CMCPE can be combined yet with highly sensitive detection in the presence of electrocatalysts [102]. Finally, even a CPbiosensor with two enzymes [180], can be quoted here as another example of multiple modification, attaining the desired sensitivity under actual conditions.…”
Section: Possible Ways Of Modifying Carbon Pastesmentioning
confidence: 99%
“…Similar procedures are being utilized in stripping analysis, where the beneficial effect of the preconcentration step at a CMCPE can be combined yet with highly sensitive detection in the presence of electrocatalysts [102]. Finally, even a CPbiosensor with two enzymes [180], can be quoted here as another example of multiple modification, attaining the desired sensitivity under actual conditions.…”
Section: Possible Ways Of Modifying Carbon Pastesmentioning
confidence: 99%
“…It is obvious that the critical step in improving both sensitivity and selectivity of LOD/HRP-modified carbon paste electrode is the effective regeneration of the active form of HRP. The effect of a mediator on the analytical performances of the bienzymatic GOD/HRP electrode has already been studied, and it has been demonstrated that the introduction of ferrocene significantly increased the amperometric response [14]. In this study, the use of ferrocene in the LOD/HRP-modified CPE was also found beneficial in terms of sensitivity because the highest response with mediated electron transfer of HRP was obtained.…”
Section: Introductionmentioning
confidence: 65%
“…Rondeau, et al [38] identified the optimal proportion of two enzymes in the biosensor composite by monitoring electrical response signals to establish idealized conditions for glucose oxidase : horseradish peroxidase immobilized with a modified carbon paste for in order to increase the selectivity, sensitivity, accuracy and stability [38]. The intensity of the electrochemical signal response was analyzed by Alpat and Telefoncu [39] who measured the amount of alcohol dehydrogenase immobilized on the electrode surface (47.1 to 200 U cm -2 ) and found that the linear response was between 0.01 mM and 0.04 mM for 117.6 U cm -2 .…”
Section: Electrochemical Behaviour Of the Biosensormentioning
confidence: 99%